Is Machine Learning Helping E-Commerce Platforms To Find What Their Customers Need? - Daniel B. FERNANDES; Miguel A. BRITO; João P. SILVA (Communications of International Proceedings, 2021)
The fundamental point of this article is to find whether machine learning created a positive impact in the e-commerce industry. First, I will give an overview in machine learning, pattern recognition and preference learning, trying to explore the current trends and its potential. After that, it is important to understand the e-commerce industry, its context and how it has developed. Lastly, this article will explore the impact that machine learning has had in e-commerce platforms throughout examples.
Keywords: Machine Learning; E-commerce.